The effects of celebrity endorsers on green and eco-friendly products - Lak, Hadı̇ Saları̇ (My University, 2015)
ÖZET Yeşil ve Çevre Dostu Ürünlerin Satışı Üzerinde Ünlülerin Etkisi Mevcut literatüre göre yeşil reklamların güvenirliği diğer reklamlara nispeten düşüktür. Pazarlama araştırmacıları her zaman müşterilerin güvensizliğini gidermek için yeni yolları araştırmaktadır. Ünlülerin etkisi reklamların inandırıcılığında ve hatırlama oranının arttırılmasında çok önemli bir etkiye sahiptir. Bu savdan yola çıkarak, bu çalışmada ünlü kişilerin yeşil ürün reklamları üzerine etkisi araştırılmıştır. Bu sebeple iki ayrı araştıma yapılmıştır: tanımlayıcı ve deneysel. Birincisinde yazar yeşil pazarlamanın bazı belirleyici faktörleri olarak tanınan sağlık bilinci, çevreye yönelik tutum ve yeşil ürünlere yönelik tutumun etkisini, yeşil reklamla yönelik tutumun üzerinde ölçmüşler. Bu faktörlerin yanısıra, ünlülerin güvenilirlik boyutları ve onların ürünlerle uyumunun etkisi, yeşil reklamla yönelik tutumun üzerinde ölçülmüştür. Nihayeten yazarlar yeşil reklamın yeşil ürüne olan tutum üzerindeki etkisini de ölçmüşler. Ankete cevap verenlerin sayısı İstanbul’da yaşayan 200 kişiden oluşmaktadır. Deneysel araştırmada yazar biri güvenilirliği yüksek diğeri beğenilen iki ünlünün etkisini MANOVA analizi kullanarak her iki ürün üzerinde test etmiştir. Etkileme analizi iki farklı boyutta yapılmıştır: yeşil reklama yönelik tutum ve sunulan ürüne yönelik tutum. Etkileme analizinin sonuçlarına göre, erkek olan (güvenilirliği yüksek) ünlünün etkisi süt reklamı üzerinde ve kadın olan (beğenilen) ünlünün etkisi buzdolabı reklamı üzerinde daha fazla açıklayıcıbulunmuştur.

THE EFFECTS OF CELEBRITY ENDORSERS ON GREEN AND ECO-FRIENDLY PRODCUTS According to previous researches the credibility of green messages are relatively low. It was always important for marketers to find some ways to solve the distrust problem of people toward green advertisements. In accordance to the literature celebrity endorsement is a good method in marketing to enhance believability and recall power of advertisements. Thus, the aim of this research is to understand the effect of celebrity endorsers on green product advertising. Two studies have been accomplished in this study: descriptive and experimental studies. In descriptive study authors explore the role of health consciousness, attitude toward green products and environmental attitude as some of determinants of green purchase behavior on attitude toward green advertisements. Alongside with this, in first study the impact of celebrity endorser’s credibility and congruency with product have been tested on attitude toward advertisement. Finally authors measured the impact of attitude toward green advertisement on attitude toward advertised product. In order to complete this task 4 questionnaires have been designed. Two different Turkish celebrities (trustworthy v. attractive) have been chosen in order to advertise two green products. The sample of study is composed of 200 people, which live in Istanbul. Second study, which was experimental, tries to understand the effectiveness of each endorser on each of the products. In order to accomplish this, MANOVA analysis accomplished and the interaction effect results show that the male (trustworthy) endorser is more effective in milk advertisement in accordance to attitude toward advertisement and attitude toward advertised products dimensions. In addition, female (attractive) endorser was effective for refrigerator advertisement in accordance to two mentioned dimensions.
Keywords: Pazarlama; Üretim yönetimi